Enantioselective synthesis of 4,5,6,7-tetrahydro-4-oxo-benzofuran-5-yl acetate and 1-benzyl-4,5,6,7-tetrahydro-4-oxo-1(H)-indol-5-yl acetate using chemoenzymatic methods - Demir, Ayhan S.; Caliskan, Zerrin; Sahin, Ertan (ELSEVIER SCIENCE BV, 2007)
The chemoenzymatic synthesis of both of the enantiomers of pharmacologically interesting compounds such as 4,5,6,7-tetrahydro-4-oxobenzofuran-5-yl acetate (2a), 4,5,6,7-tetrahydro-4-oxo-6,6-dimethylbenzofuran-5-yl acetate (2b), and their hydroxy derivatives 3a, 3b, 1-benzyl4,5,6,7-tetrahydro-4-oxo-1(H)-indol-5-yl acetate (5), starting from 6,7-dihydrobenzofuran-4(5H)-one (la), 6,7-dihydro-6,6-dimethylbenzofuran4(5H)-one (7b), and 1-benzyl-6,7-dihydro-1 H-indol-4(5H)-one (4) are reported. Manganese(III) acetate-mediated acetoxylation followed by the enzyme-mediated kinetic resolution of alpha'-acetoxy enone provides acetoxy and hydroxy derivatives in good yields and high enantiomeric excesses. (c) 2006 Elsevier B.V. All rights reserved.
Keywords: manganese(III) cetate; indole; benzofurane; enzymatic resolution; oxidation of enone; 4-OXO-4,5,6,7-TETRAHYDROINDOLES; INDOLES; SUBSTITUENTS; ENANTIOMERS; ENONES; Biochemistry & Molecular Biology; Chemistry